Clinical Neuropsychology as a Specialist Profession in European Health Care: Developing a Benchmark for Training Standards and Competencies Using the Europsy Model? - Hokkanen, Laura; Barbosa, Fernando; Ponchel, Amélie; Constantinou, Marios; Kosmidis, Mary H.; Varako, Nataliya; Kasten, Erich; Mondini, Sara; Lettner, Sandra; Baker, Gus; Persson, Bengt A.; Hessen, Erik (Frontiers in Psychology, 2020)
The prevalence and negative impact of brain disorders are increasing. Clinical Neuropsychology is a specialty dedicated to understanding brain-behavior relationships, applying such knowledge to the assessment of cognitive, affective, and behavioral functioning associated with brain disorders, and designing and implementing effective treatments. The need for services goes beyond neurological diseases and has increased in areas of neurodevelopmental and psychiatric conditions, among others. In Europe, a great deal of variability exists in the education and training of Clinical Neuropsychologists. Training models include master’s programs, continuing education courses, doctoral programs, and/or post-doctoral specialization depending on the country, with no common framework of requirements, although patients’ needs demand equal competencies across Europe. In the past five years, the Standing Committee on Clinical Neuropsychology of the European Federation of Psychologists’ Association has conducted a series of surveys and interviews with experts in the field representing 30 European countries. The information, along with information from the existing literature, is used in presenting an overview of current and relevant topics related to policy and guidelines in the training and competencies in Clinical Neuropsychology. An option for the way forward is the EuroPsy Specialist Certificate which is currently offered in Work- and Organizational psychology and Psychotherapy. It builds upon the Basic Certificate and complements national standards without overriding them. General principles can be found that can set the basis for a common, solid, and comprehensive specialty education/training, sharpening the Neuropsychologists’ competencies across Europe. The requirements in Clinical Neuropsychology should be comparable to those for the existing specialty areas in the EuroPsy model. Despite the perceived challenges, developing a Specialist Certificate appears a step forward for the development of Clinical Neuropsychology. Recommendations are proposed towards a shared framework of competencies by the means of a common level of education/training for the professionals in Europe. Benchmarking training standards and competencies across Europe has the potential of providing protection against unqualified and ethically questionable practice, creating transparency, raising the general European standard, and promoting mobility of both Clinical Neuropsychologists and patients in Europe, for the benefit of the professional field and the population.